2008
DOI: 10.1159/000169658
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Increases Erythropoietin-Stimulating Agent Hyporesponsiveness in Maintenance Hemodialysis Patients: Role of Anti-Inflammation Effects

Abstract: Erythropoietin-stimulating agent (ESA) hyporesponsiveness is aggravated by chronic inflammation in maintenance hemodialysis (MHD) patients. Dyslipidemia is prevalent in MHD patients. Statin therapy has been demonstrated to not only be effective in lowering lipid levels, but also numerous pleiotropic effects including anti-inflammatory, anti-fibrotic and endothelial function improvement. Recently, a retrospective study has shown that statin therapy decreases ESA requirements in MHD patients. We conducted a pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 56 publications
4
26
2
1
Order By: Relevance
“…Our results that elevated EPO levels were in large part related to the level of inflammation are in line with the described mechanisms. Interestingly, recent reports demonstrated diminished EPO resistance after statin treatment potentially through pleiotropic "inflammation-lowering" effects (27,28). However, in our study we could not detect any effect of statin treatment on the described associations.…”
Section: Discussioncontrasting
confidence: 91%
“…Our results that elevated EPO levels were in large part related to the level of inflammation are in line with the described mechanisms. Interestingly, recent reports demonstrated diminished EPO resistance after statin treatment potentially through pleiotropic "inflammation-lowering" effects (27,28). However, in our study we could not detect any effect of statin treatment on the described associations.…”
Section: Discussioncontrasting
confidence: 91%
“…This study showed a positive significant association between statins use and ERI. This comes in agreement with several studies because of statins' pleiotropic properties that reduce inflammation [59][60][61]. By contrast, others [62] failed to show a statistical significant decrease in the CRP levels, suggesting a mechanism other than decrease in inflammation for the reduction of ERI.…”
Section: Individual Response Variations To Erythropoietin Stimulatingsupporting
confidence: 91%
“…29 Optimizing adequacy of dialysis or switching patients to alternative modalities, such as peritoneal dialysis 30 or nocturnal 31 hemodialysis, may also result in lower ESA dosage. Treating inflammation either with drugs, such as pentoxyfilline 32 or a statin, 33 or treating an underlying infection or treating hyperparathyroidism also seem effective in reducing ESA dosage without causing the Hb to fall. For some patients who are waiting for a kidney allograft, long-term ESA therapy will be necessary because blood transfusion must be avoided to minimize the risk for sensitization.…”
mentioning
confidence: 99%